Estimating the veteran effect with endogenous schooling when instruments are potentially weak - Saraswata Chaudhuri; Elaina Rose (Institute for the Study of Labor (IZA), 2009)
Instrumental variables estimates of the effect of military service on subsequent civilian earnings either omit schooling or treat it as exogenous. In a more general setting that also allows for the treatment of schooling as endogenous, we estimate the veteran effect for men who were born between 1944 and 1952 and thus reached draft age during the Vietnam era. We apply a variety of state-of-the-art econometric techniques to gauge the sensitivity of the estimates to the treatment of schooling. We find a significant veteran penalty.
urn:nbn:de:101:1-20090615185
Keywords: C2; J24; 330; Veteran effect; weak instruments; Einkommen; Bildungsertrag; Soldaten; Wehrdienst; USA